Role of Serum Albumin Aggregation in Lubrication and Wear Protection of Shearing Surfaces - Samak, Mihir (Université d'Ottawa / University of Ottawa, 2019)
Healthy articular joints exhibit remarkable lubrication due in large part to the complex rheological and tribological behavior of the synovial fluid (SF) that lubricates the joints. Current approaches that seek to elucidate such remarkable lubrication usually focus on the roles of high molecular weight SF components such as lubricin and hyaluronic acid but frequently overlook the role of serum albumin (SA), although it represents 90% of the protein content of SF. In this thesis, we used the Surface Forces Apparatus to investigate in detail the structural and tribological response of SA thin films when sheared between model surfaces and subjected to a large range of shearing parameters. Our data indicate that, under shear, SA films reproduce closely the shear response previously reported for SF, i.e., film thickening and formation of numerous long-lived aggregates accompanied by low friction and efficient surface protection against damage. More specifically, our detailed investigation of shear parameters reveals that (i) strong anchoring of SA to surfaces promotes the formation of large rod-like shaped aggregates that enable rolling friction and keep surfaces far apart, preventing damage, (ii) aggregation mechanism is irreversible, which makes aggregates long-lived (though mobile) in the contact, and (iii) aggregate formation only occur when SA was sheared above a ‘critical’ amplitude Ac and a critical shear velocity Vc. Collectively, our results provide experimental evidence of the role of globular proteins, such as SA, in lubrication and establish a correlation between shearing parameters, formation and stability of aggregates, low friction and wear protection. Although our findings are based on experiments involving rigid, nonporous surfaces hence can hardly be generalized to compliant and porous cartilage surfaces, they are applicable to other rigid tribosystems such as artificial joints and will certainly advance our understanding of joint implants’ lubrication in SF mediated by protein aggregation, with implications for future design of artificial joints and therapeutic interventions.
Keywords: serum albumin; surface forces apparatus; tribology; biolubrication; protein aggregation